Open Order Due Date Maintenance in MRP Systems - Penlesky, Richard J.; Berry, William L.; Wemmerlöv, Urban (Management Science, 1989)
This paper is concerned with the problem of maintaining open order due dates in job shops that plan and schedule their operations using Material Requirements Planning (MRP) methodology. Two different techniques for dealing with open order due date changes are analyzed using customer service level and total inventory level performance measures. With the first technique, called the fixed due date approach, due dates are never changed from those originally assigned to orders when released to the shop. With the second technique, called the dynamic due date approach, all due dates are updated to reflect actual need dates. Beyond evaluating them in an MRP context, this study extends current understanding of these two techniques by observing them in a variety of different operating environments. The results of the study indicate that: (1) the dynamic due date approach performs as good as, or better than, the fixed due date approach across a wide range of operating conditions; and (2) operating conditions have an important effect on the magnitude of the performance differential between the two approaches.